ALSUntangled #62: vitamin C. Issue 5 (3rd July 2022) - Bedlack, Richard; Barkhaus, Paul; Carter, Greg; Crayle, Jesse; Mcdermott, Christopher; Pattee, Gary; Polak, Meraida; Salmon, Kristiana; Wicks, Paul
Abstract: Vitamin C is one of the most common supplements taken by people with ALS. As an antioxidant, it has a plausible mechanism for slowing disease progression and there are some flawed pre-clinical studies and case reports suggesting benefit. However, a small human trial showed no benefit. Given this negative trial, we do not currently advise vitamin C as an ALS treatment.